Electron beam surface melting of MoSiBTiC alloys: Effect of preheating on cracking behavior and microstructure evolution. (1st November 2021) - Higashi, Masaya; Yoshimi, Kyosuke
Graphical abstract: Highlights: Crack-free MoSiBTiC alloy could be processed via electron beam melting (EBM). Crack density decreased with increasing the preheating temperature. In-situ heating effects as well as initial preheating suppressed cracking. Various microstructures developed depending on scanning and preheating conditions. Abstract: In order to investigate the feasibility of the electron beam melting (EBM) process for fabricating brittle Mo-Si-B based alloys, the effect of preheating on cracking behavior and microstructure evolution was systematically investigated using two different MoSiBTiC alloys. Single track and multi tracks were scanned on the cast MoSiBTiC alloy substrates with and without preheating. In the single-track scanning, the crack density significantly decreased with increasing preheating temperature; however, only tiny cracks remained even at high preheating temperature of 1250 °C. In contrast, the application of multi-track scanning with preheating, which more closely resembles the actual EBM building process, enabled complete cracking suppression regardless of the same beam parameter. The surface and cross-sectional microstructure observation revealed that the difference in cracking behavior between single-track and multi-track scanning is due to the decrease in cooling rate by in-situ heating effects through successive track scanning in addition to initial preheating. Moreover, it was confirmed that the cracking could be prevented even in the case of a very brittle intermetallic phase (Mo5 SiB2 )-matrix MoSiBTiC alloy. This groundbreaking result expands the possibilities of using EBM for the manufacturing of promising ultrahigh-temperature and high-strength materials, which have been unable to be processed by conventional routes.